Relationship among perceived stress, anxiety, depression and craniocervical pain in nursing professionals under stress at work - Pozzebon, Daniela (2017)
Introduction: The appearance and evolution of some clinical pain conditions may be influenced by stress and other psychosocial factors. Face, head and cervical muscles may increase their activity and tension in the presence of stress, leading to craniocervicomandibular pain in individuals exposed to stress. Objective: To assess the relationship among perceived stress, anxiety, depression and craniocervicomandibular pain in nursing professionals under stress at work. Materials and Methods: Forty-three women under stress at work, according to the Job Stress Scale (JSS), were assessed by the Perceived Stress Scale (PSS), the Hospital Anxiety and Depression Scale (HADS), pressure pain threshold, measured by algometry, and muscle sensitivity to hand palpation of the masticatory and cervical muscles. Results: A low moderate level of perceived stress was found in 62.79% of the sample, anxiety in 11.63% and depression in 9.30%. The psychosocial scales correlated with each other. No correlation was found between pressure pain threshold and perceived stress, anxiety and depression. The level of pain to hand palpation correlated with the perceived stress scores. Conclusion: Pressure pain threshold was not influenced by the psychosocial factors assessed. Pain intensity to hand palpation, however, was higher as the perception of stress increased.